Análisis de las especificaciones PAS-55:2008 como aporte a la gestión de activos físicos en las ensambladoras automotríces del Ecuador - Novillo Novillo, Alex Javier (2014)
This research paper entitled "Analysis of the PAS-55 specifications: 2008 as a contribution to the management of physical assets in automotive assembly plants of Ecuador" arises from the need for management tools worldwide that can be used Automotive assemblers in Ecuador to ensure the sustainability and optimum performance of its fixed assets. The research process begins with the study of the PAS-55: 2008 and the management of physical assets, and then analyze the automotive assemblers which will host Ecuador in field research focused on determining the contributions they can provide these specifications. Automotive assembly plants are rich in assets, many of which are critical for the assembly of vehicles